2012
DOI: 10.3133/ofr20121242
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic analysis of the river response to sedimentation downstream of Mount Rainier, Washington

Abstract: A study of the geomorphology of rivers draining Mount Rainier, Washington, was completed to identify sources of sediment to the river network; to identify important processes in the sedimentdelivery system; to assess current sediment loads in rivers draining Mount Rainier; to evaluate if there were trends in streamflow or sediment load since the early 20th century; and to assess how rates of sedimentation might continue into the future using published climate-change scenarios. Rivers draining Mount Rainier car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 76 publications
0
27
0
Order By: Relevance
“…Our analysis of temporal changes in flood magnitude showed that Q2 (two‐year‐flood) values were relatively low in the late 1960s and early 1970s, but increased thereafter (Figures , A6), consistent with previous findings of greater flood magnitude and frequency in recent decades in this region (Piety et al , ; Bountry et al , ; Beschta and Ripple, ; Czuba et al ., ; Tohver et al ., ). The Q2 magnitudes over the most recent ~4 decades have been 10–35% greater than over the entire length of each stream‐gage record.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Our analysis of temporal changes in flood magnitude showed that Q2 (two‐year‐flood) values were relatively low in the late 1960s and early 1970s, but increased thereafter (Figures , A6), consistent with previous findings of greater flood magnitude and frequency in recent decades in this region (Piety et al , ; Bountry et al , ; Beschta and Ripple, ; Czuba et al ., ; Tohver et al ., ). The Q2 magnitudes over the most recent ~4 decades have been 10–35% greater than over the entire length of each stream‐gage record.…”
Section: Resultsmentioning
confidence: 98%
“…The lowest annual flows occur in September. Flood magnitude typically fluctuates over decadal scales, due in part to Pacific Decadal Oscillation (PDO) cycles (Mantua et al , ; Czuba et al , ). Flood magnitude and frequency generally have been greater in Pacific Northwest rivers since the late 1970s than over the period of record as a whole (Piety et al , ; Bountry et al , ; Beschta and Ripple, ; Czuba et al , ; Tohver et al , ).…”
Section: Study Areamentioning
confidence: 99%
“…For example, alluvial sections of gravel-bed rivers subject to increased bedload and aggradation often respond with channel widening and increased braiding (Leopold and Maddock, 1953;Lyons and Beschta, 1983;Knighton, 1989;Madej and Ozaki, 1996;Miller and Benda, 2000;Lauer et al, 2008;Pierson et al, 2011;Czuba et al, 2012). For natural river systems where new sediment is sourced from the upper watershed or from upstream channel migration, increased bedload is usually associated with large flood events.…”
Section: Introductionmentioning
confidence: 96%
“…The dominant source of the inorganic sediment at SG is likely tidal and not riverine material as there is limited sediment available from the Nisqually River, due to the upstream La Grande and Alder dams. Such restriction of river flow results in only about 10% of the total sediment load of the Nisqually River reaching Puget Sound on any given year (Czuba et al ; Curran et al ), resulting in a shortage of sediment available for marsh‐building at the river mouth.…”
Section: Discussionmentioning
confidence: 99%